Bitcoin, Lifecoin, Namecoin: The Legal Nature of Virtual Currency - KIRILLOVA, Elena Anatolyevna; PAVLYUK, Albert Valentinovich; MIKHAYLOVA, Irina Aleksandrovna; ZULFUGARZADE, Teymur E.; ZENIN, Sergey Sergeevich (Journal of Advanced Research in Law and Economics; Vol 9 No 1 (2018): JARLE Volume IX Issue 1(31) Spring 2018DO - 10.14505//jarle.v9.1(31).16, 2018)
The current article examines the peculiarities and legal nature of Bitcoin, Lifecoin, Namecoin, Quark, WebMoney, Ripple and other virtual currencies. There is no single understanding of the legal essence of virtual currency in the world today; therefore, the legal status of such currencies is not officially fixed and there are no official rates of Bitcoins or other crypto currencies against national currencies. Their rate is determined in the course of trading at virtual Bitcoin exchanges and exchange platforms. Such a situation is dictated by the novelty of legal relations in the field of crypto currency circulation, the risks of their implementation, as well as security problems. The main goal of the study is to define the legal nature and features of virtual currencies and the possibilities of legislative regulation of using crypto currencies. When writing the article, the methods of collecting and studying singularities have been used, as well as generalization methods, the methods of scientific abstraction, and the methods of studying regularities. The study has concluded that it is advisable to provide for the licensing of mining and crypto trading at the international level, customers should be identified when selling and buying virtual currencies, introducing a special verification procedure for Bitcoin users will prevent the abuse of virtual currencies for money laundering and terrorism financing. As a result of the analysis, a definition has been given, and the main features and functions of the virtual currency have been highlighted. It has been proved that virtual currencies are a new kind of electronic money stored in computer memory, the monetary value of the virtual currency is managed by means of a technical device. Virtual currency is a new means of payment and does not require access to deposit accounts.